Information management in health services (Buckingham : Open University Press, 1994)
Overview: information policy and the market. The practitioner perspective. The academic perspective.
Keywords: Great Britain; Health services; NHS; Health services administration -- Great Britain; National Health Service (Great Britain); Information storage and retrieval systems -- Health services administration -- Great Britain; Information resources management